The Link Between Personal Values and Frequency of Drinking Depends on Cultural Values: A Cross-Level Interaction Approach - Rudnev, Maksim; Vauclair, Christin-Melanie (Frontiers in Psychology, 2018)
The increasing availability of large cross-national datasets enables researchers to integrate micro and macro levels of relations between human values and behavior. Particularly interesting are interactions between personal and cultural levels which can demonstrate to what extent a specific behavior is affected by individual values and cultural context. In this study, we aimed to shed light on this issue by analyzing data on basic values and drinking behavior from 21 national representative samples of the European Social Survey (2014). The results of multilevel regressions showed that country-level effects of Openness to Change (vs. Conservation) or Self-Transcendence (vs. Self-Enhancement) were not significantly related to frequency of drinking. As expected, individual-level Openness to Change (vs. Conservation) was consistently positively related to drinking frequency, whereas Self-Transcendence (vs. Self-Enhancement) was not. Contrary to our hypothesis, there was a positive association between personal Self-Transcendence (vs. Self-Enhancement) values and frequency of drinking in countries putting higher importance on extrinsic motivations (i.e., Conservation or Self-Enhancement values), while this link was less positive or even negative in countries valuing intrinsic motivations (i.e., Openness to Change or Self-Transcendence values). Moreover, a marginally significant interaction between individual- and country-level Openness to Change (vs. Conservation) values supported the same counter-intuitive result. These findings challenge the widespread idea that more conservative societies attenuate the link between personal values and behavior. In contrast, self-affirmation and cultural rewards theories, as well as culture-specific value instantiations, may explain these results. This study shows that the value-behavior link differs across cultures, yet in a more complex way than was assumed so far. This opens up new possibilities for research on values and behavior in a cross-cultural context.